Viral dynamics in a high-rate algal pond reveals a burst of Phycodnaviridae diversity correlated with episodic algal mortality - E. E. Chase; T. Pitot; S. Bouchard; S. Triplet; C. Przybyla; A. Gobet; C. Desnues; G. Blanc (mBio)
ABSTRACT This study explores virus-host dynamics in a unique environment: an industrial high-rate algal pond (HRAP). A wealth of novel DNA algal viruses are revealed, including members of Nucleocytoviricota “giant viruses” and the enigmatic Preplasmiviricota (e.g., virophages and polinton-like viruses). Several species of single-celled eukaryotic photosynthetic algae are identified (Chlorophyta) as putative hosts, with alternating dominant populations during the year of study. We specifically observe a surprising diversity of giant viruses from the family Phycodnaviridae (Nucleocytoviricota), including phylogenetically related but highly diversified genotypes appearing in the HRAP that we suggest are implicated in bloom collapse. We hypothesize that these related Phycodnaviridae lineages infect the same algal species of the genus Picochlorum that has been identified in the HRAP. This study establishes a baseline for comprehending the role viruses play in algal farming and emphasizes the necessity of controlling the viral load in future culture system development to optimize algal growth.IMPORTANCEThe virosphere is ubiquitous, but we have yet to characterize many environments where viruses exist. In an industrial polyculture of microalgae, a wealth of viruses persist, their diversity and dynamics changing over time and consequently give evidence of their evolution and ecological strategies. Several notable infectious agents of the culture’s algae appear, including giant viruses, polinton-like viruses, and a virophage. As our reliance and interest in algal compound-based cosmetics, pharmaceuticals, and bio-plastics increases, so must our understanding of these systems, including the unique viruses that appear there.